Efektivitas Variasi Ukuran Botol Media Tanam Terhadap Pertumbuhan Planlet Anggrek Phalaenopsis amabilis L. - Dewi, Aulia Widiawati Fitriana; Rahayu, Praptining; Dewi, Endah Rita Sulistya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of variations in media bottle size on the growth of Phalaenopsis amabilis L. orchid plantlets. This study used a Completely Randomized Design (CRD) with variations in one factor, namely the size of the media bottle (P1: 250 ml, P2: 500 ml, and P3: 750 ml). Each treatment variation was repeated four times. The results of data analysis in this study used the SPSS 27 program. The data was tested for normality and homogeneity, then continued with the ANOVA (Analysis of Variance) test at the 5% level. If there is a significant influence then proceed with the Least Significant Difference (BNT) test. The results of the research showed that there was an effect of using variations in the size of the 750 ml bottle on the parameters of root length and number of roots. In conclusion, variations in the size of the planting medium bottle can influence the growth of Phalaenopsis amabilis L. orchid plantlets including root length and number of roots. Keywords: Tissue Culture, Phalaenopsis amabilis L., Bottle Size